STUDING THE PRINCIPAL VARIABLES AT THE AUDITORIUM ROOMS TO SPECIFY THE COUSTIC PERFORMANCE EFFECIENCY - Ezzy, Nidaa (Anbar Journal of Engineering Science, 2008)
The complete of the architectural space consider the most interested side in meanings and what it contain . it is the space where the basic stamp for the architecture formation achieved as the acoustic performance was one of the functional articles that belong to some architectural spaces style , the research choose two rooms belong to the institute used as auditorium to study its efficiency about the availability of some important acoustic indicators that should be available in such kind of auditoriums to achieve the connection between the engineering design and the acoustical design for the auditorium elements to reach the required performance for the room to give comfortable impression . the research see to study some of the following indicators :- 1. Reverberation Time. 2. Loudness. 3. intelligibility of Speech and Articulation.